A Life Course Perspective on the Income-to-Health Relationship: Macro-Empirical Evidence from two Centuries - Korbinian Nagel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The epidemiological literature discusses two contrary hypotheses that can represent the income-to-health relationship from a life course perspective: the ``cumulative advantage'' and the ``age as leveller'' hypothesis. The aim of this study is to transfer the investigation of both hypotheses to a macro level with long time horizon. It asks whether increases in per capita income improves population health and whether the improvements differ across population age groups. Using an unbalanced panel data set with 20 countries and with up to 211 years, the analysis relies on the Westerlund (2007) error correction methodology to detect long-run causality and on the Pesaran (2006) framework to quantify the effect magnitude. A significant effect of per capita income on survivability is only found for middle age groups. The analysis detects no significant effect on survivability of the very young and of old ages. These findings provide evidence for both hypotheses during several stages of life: while the ``cumulative advantage'' theory serves for describing the transition from young to middle ages, the transition from middle to old ages corresponds to the ``age as leveller'' mechanism.
Keywords: I15; J11; C22; 330